The Role of Services for Manufacturing Firms' Exports - Magnus Lodefalk (Örebro University School of Business, 2012)
Manufacturing firms increasingly focus on services. This trend is evident in their composition of input, in-house production and seemingly also in total sale. Firms' services intensity may affect their productivity, and thereby competitiveness abroad. Services are also instrumental in connecting to the foreign market and can help firms to differentiate their offers. However, only bits and pieces of the relation between services and manufacturing's exports have been analysed in previous literature. This study contributes by discussing the role of services for the firm, arriving at some conjectures and testing them empirically. Export intensity is regressed on two services parameters, applying a fractional model to a rich panel of firms in Sweden in the period 2001-2007. The microeconometric results suggest that there is an effect of services inputs, while controlling for covariates and firm heterogeneity. Raising the proportion of services in in-house production, on average, yields higher export intensity. Buying-in more services is associated with higher export intensity for firms in selected industries. Overall, the study provides new firm-level evidence of the role of services as inputs in manufacturing.
Keywords: F14; L24; L25; L60; O33; 330; firm; export intensity; manufacturing; services; intangibles; innovation